Proceedings of the 2018 3rd International Conference on Modelling, Simulation and Applied Mathematics (MSAM 2018) 2018
DOI: 10.2991/msam-18.2018.25
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Fluctuation of Chinese Crude Oil Futures- Based on GARCH-type Model

Abstract: On March 26, 2018, Chinese crude oil futures start online trading in Shanghai futures exchange, a subsidiary of Shanghai international energy trading center. Chinese crude oil futures are expected to balance the current benchmark prices of WTI and brent .This study aims at analyzing the Chinese high frequency crude oil price. In this study, GARHC-type models are used namely GARCH and TARCH for modelling the high frequency Chinese crude oil yield. It is concluded that the TARCH model performs well as compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…At present, more and more scholars study China's crude oil futures, China's crude oil market environment and oil policy. Sun et al (2018) used GARCH and TARCH models to study the fluctuation characteristics of China's crude oil futures returns rate based on high-frequency data, and they found that the changes of China's crude oil futures returns rate in the current as well as the lag period were mainly influenced by itself, and the influence coefficient of one period lag was larger and the influence time was longer. Ji and Zhang (2019) analyzed the initial characteristics of China's crude oil futures market, laying a good foundation for subsequent studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, more and more scholars study China's crude oil futures, China's crude oil market environment and oil policy. Sun et al (2018) used GARCH and TARCH models to study the fluctuation characteristics of China's crude oil futures returns rate based on high-frequency data, and they found that the changes of China's crude oil futures returns rate in the current as well as the lag period were mainly influenced by itself, and the influence coefficient of one period lag was larger and the influence time was longer. Ji and Zhang (2019) analyzed the initial characteristics of China's crude oil futures market, laying a good foundation for subsequent studies.…”
Section: Literature Reviewmentioning
confidence: 99%